“Their skirts are too short!” and “He’s gay!”. Backlashes on Transnational Popular Culture Consumption in BlackPink and Bright’s Case Studies - Ghaziah Nurika Akhni (IKAT: The Indonesian Journal of Southeast Asian Studies, 2022)
The internet era has facilitated online streaming and social media platforms to burgeon, causing the flow of transnational pop cultures across regions and also offering diverse consumption of media content from around the globe. In Indonesia, the discussion on pop culture has often been centered on the proliferation of K-Pop's popularity among local audiences. Besides, the Boys Love (BL/Y) series from Thailand has also gained considerable interest in the last couple of years. While the consumption of K-Pop and Thailand's BL series in global mediascape is widely accepted without much controversy, incongruous feedbacks are present among Indonesian audiences, particularly pointing at the clash of ideological perspectives between its Muslim conservatives and the youth. The conservative group considers the media contents "vulgar" and "too liberal," while the latter defends them as part of contemporary youth culture and the freedom of expression. This paper then examines two study cases: Shopee's advertisement featuring the K-Pop group, BlackPink, and the case of Ruangguru's ambassador from Thailand, Bright Vachirawit. This paper uses qualitative textual analysis to focus on the two contested ideas (global versus local). The findings illustrate how BlackPink's female bodies and Bright's fluid identity as a lead actor in the BL series have been stigmatized and adjusted to become more acceptable commodities among pious audiences. This study helps to reveal the complexity of global consumption in a Muslim majority country where audiences' cultural identity construction has always been contested. Furthermore, it provides a glimpse of Indonesian society's current perspectives on gender and tolerance.